Television programs presented to children on the MBC3 channel: an analytical study of the reality of television content and programs - neghimech el hamami el zouiaa, hachem ahmed (Journal of Social Sciences and Humanities, 2016)
<section class="text-token-text-primary w-full focus:outline-none [–shadow-height:45px] has-data-writing-block:pointer-events-none has-data-writing-block:-mt-(–shadow-height) has-data-writing-block:pt-(–shadow-height) [&:has([data-writing-block])>*]:pointer-events-auto [content-visibility:auto] supports-[content-visibility:auto]:[contain-intrinsic-size:auto_100lvh] R6Vx5W_threadScrollVars scroll-mb-[calc(var(–scroll-root-safe-area-inset-bottom,0px)+var(–thread-response-height))] scroll-mt-[calc(var(–header-height)+min(200px,max(70px,20svh)))]" dir="auto" data-turn-id="request-WEB:08454976-c02f-4623-95a4-7f2531db39d5-18" data-testid="conversation-turn-38" data-scroll-anchor="false" data-turn="assistant"> <div class="text-base my-auto mx-auto pb-10 [–thread-content-margin:var(–thread-content-margin-xs,calc(var(–spacing)*4))] @w-sm/main:[–thread-content-margin:var(–thread-content-margin-sm,calc(var(–spacing)*6))] @w-lg/main:[–thread-content-margin:var(–thread-content-margin-lg,calc(var(–spacing)*16))] px-(–thread-content-margin)"> <div class="[–thread-content-max-width:40rem] @w-lg/main:[–thread-content-max-width:48rem] mx-auto max-w-(–thread-content-max-width) flex-1 group/turn-messages focus-visible:outline-hidden relative flex w-full min-w-0 flex-col agent-turn"> <div class="min-h-8 text-message relative flex w-full flex-col items-end gap-2 text-start break-words whitespace-normal outline-none keyboard-focused:focus-ring [.text-message+&]:mt-1" dir="auto" tabindex="0" data-message-author-role="assistant" data-message-id="780cf325-e1e3-44cf-8ff5-24d0991ba943" data-message-model-slug="gpt-5-3-mini" data-turn-start-message="true"> This study addresses the topic of television content and programs designed for children on satellite channels targeting young audiences, taking the channel (MBC3) as a representative sample of such channels. The study examines the reality of the materials and television programs broadcast by this channel to children, as it is considered a children-oriented channel. The research problem was formulated around the following main question: What is the reality of television content presented to children on the MBC3 channel? The study reached several findings, including that MBC3 presents its television content for children in seven artistic formats: animated series (cartoons), live-action films, competition programs, dramatic series, animated films (cartoons), audience participation programs, and various entertainment programs. The channel broadcast its Arabic-language content for a total of 6,980 minutes, representing 69.24% of the research sample. Meanwhile, English-language content occupied 1,550 minutes, representing 15.37%. Furthermore, MBC3 presented its television content predominantly in recorded form, with 9,980 minutes, representing 99% of the total analyzed content. In contrast, live broadcast content accounted for 100 minutes, representing 0.99% of the research sample. <div class="pointer-events-none translate-y-(–scroll-root-safe-area-inset-bottom) R6Vx5W_threadScrollVars min-h-(–gutter-remaining-height,0px) group-data-stream-active/scroll-root:h-[calc(var(–thread-response-height)-16*var(–spacing))]">